Assessment of β-D-Glucosidase Activity from Two Typical Strains of the Lactic Acid Bacteria, Oenococcus oeni, in China - Li, Y.H.; Fan, M.T.; Zhang, G.Q.; Liu, Y.L. (South African Journal of Enology and Viticulture, 2016)
β-D-glucosidase (βG) is one of the most interesting glycosidases for the hydrolysis of glycoconjugated precursors to release active aromatic compounds in musts and wines. Oenococcus oeni strains SD-2a and 31MBR are widely used in Chinese wines to reduce the acidity. In the present study, the βG activity of the two strains was localised and partially characterised using synthetic substrate. The activity occurred in whole cells, sonication supernatants and debris, but not in the culture supernatants for both strains. Whole cells of strain SD-2a possessed greater βG activity, while strain 31MBR showed higher enzyme activity in the sonication supernatants. Strain 31MBR exhibited higher total enzyme activity than strain SD-2a. The optimum temperatures for βG from the two strains were 40ºС at pH 3.5 and 50ºС at pH 5.0, respectively. Ethanol at low concentrations had a positive effect on βG activity in both strains, while a wine-like pH (3.5) decreased the enzyme activity to a great extent. Whole cells of strain SD-2a showed the highest activity among all samples tested under wine-like conditions. Thus, strain SD-2a proved to have potential for aroma improvement in winemaking.